2014
DOI: 10.1002/etc.2743
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid sequence of the AhR1 ligand‐binding domain predicts avian sensitivity to dioxin like compounds: In vivo verification in European starlings

Abstract: Research has demonstrated that the sensitivity of avian species to the embyrotoxic effects of dioxin-like compounds can be predicted by the amino acid identities at two key sites within the ligand-binding domain of the aryl hydrocarbon receptor 1 (AhR1). The domestic chicken (Gallus gallus domesticus) has been established as a highly sensitive species to the toxic effects of dioxin-like compounds. Results from genotyping and in vitro assays predict that the European starling (Sturnus vulgaris) is also highly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…Dose–response curves for early life stage mortality that were predicted using EC Threshold or EC50 as input variable in the corresponding qAOPs were validated against 25 experimental dose–response curves from the published literature that reported measured concentrations and percentage of mortality for each dose (Brunstrom and Reutergardh 1986; Brunstrom and Lund 1988; Brunstrom 1989, 1990; Spitsbergen et al 1991; Walker et al 1994; Walker and Peterson 1994; Powell et al 1996, 1998; Elonen et al 1998; Hoffman et al 1998; Cohen‐Barnhouse et al 2011; Eng et al 2014, 2017; Tillitt et al 2017). These 25 scenarios represent 9 species of birds, 7 species of fish, and 5 different DLCs.…”
Section: Methodsmentioning
confidence: 99%
“…Dose–response curves for early life stage mortality that were predicted using EC Threshold or EC50 as input variable in the corresponding qAOPs were validated against 25 experimental dose–response curves from the published literature that reported measured concentrations and percentage of mortality for each dose (Brunstrom and Reutergardh 1986; Brunstrom and Lund 1988; Brunstrom 1989, 1990; Spitsbergen et al 1991; Walker et al 1994; Walker and Peterson 1994; Powell et al 1996, 1998; Elonen et al 1998; Hoffman et al 1998; Cohen‐Barnhouse et al 2011; Eng et al 2014, 2017; Tillitt et al 2017). These 25 scenarios represent 9 species of birds, 7 species of fish, and 5 different DLCs.…”
Section: Methodsmentioning
confidence: 99%
“…Other birds classified as semisensitive were Tachycineta bicolor , Troglodytes aedon, and Phalacrocorax sp. Although experimental studies focusing on the reproductive effects of PCB residues in eggs have been performed on species classified as highly sensitive (e.g., European starling ( Sturnus vulgaris ) or the gray catbird ( Dumetella carolinensis )), , field monitoring data on these species was grossly lacking. This implies that our SSDs most likely underestimate the effects of dioxin-like PCBs toward birds.…”
Section: Discussionmentioning
confidence: 99%
“…European starlings are particularly useful as a study species because their ecology and physiology are well studied, they can be attracted to and reared in nest boxes, and they are amenable to captivity. Starlings have also been used widely in ecotoxicology studies and have recently been identified as a highly sensitive species given the structural affinity of their aryl hydrocarbon receptor to bind strongly to dioxin‐like compounds, including certain hydroxylated PCBs .…”
Section: Discussionmentioning
confidence: 99%